Requirement model for Maktab Rendah Sains MARA (MRSM) homeroom system - R.Rama, Thanaletchimi; Omar, Mazni (2006)
Requirement is an important part to develop a system.Defining the requirement will determine the successful or failure of the system.Therefore, defining the requirement is the step in the system design process.Requirement model techniques are used to model out all the requirements.Requirements model will be used to discover and clarify the functional and data requirements for software and business systems.This project aims to create a requirement model for Homeroom systems (RMHS) using Unified Modeling Language (UML) and validate through horizontal prototype.The requirement model consists of use case diagram, use case specification, class diagram, sequence diagram, collaboration diagram, activity diagram and list of requirements.Lastly, this requirement model will be guidelines to other researcher who doing similar systems.